2017
DOI: 10.1111/emre.12135
|View full text |Cite
|
Sign up to set email alerts
|

The Inverted U‐Shaped Hypothesis and Firm Environmental Responsiveness: The Moderating Role of Institutional Alignment

Abstract: The impact of regulatory coercion on firm environmental responsiveness is well discussed by institutional theorists. The intuitive nature of the relationship is positive and monotonic, that is, the continuous strengthening of regulatory coercion prompts top management to be more environmentally responsive. This paper shows that: (1) overall, there is an inverted U‐shaped relationship between regulatory coercion and firm environmental responsiveness, that is, the continuous strengthening of regulatory coercion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 125 publications
(161 reference statements)
0
4
0
Order By: Relevance
“…The newly introduced concept can be beneficial in highlighting the heterogeneity across different organizations when it comes to climate change disclosure and addressing some conflicting findings stemming from the extant scholarship. Second, we gather evidence from different streams of literature, including sustainability reporting (Boura et al, 2020; Cabeza‐García et al, 2018), strategic leadership (Papagiannakis & Lioukas, 2018; Yamak et al, 2019), environmental management (Eiadat & Fernández Castro, 2018), and more, providing a holistic understanding of climate change disclosure. Third, although we find that the outcome dimension is less examined compared with the antecedent dimension, we highlight some critical gaps in both that suggest a future research agenda.…”
Section: Discussionmentioning
confidence: 99%
“…The newly introduced concept can be beneficial in highlighting the heterogeneity across different organizations when it comes to climate change disclosure and addressing some conflicting findings stemming from the extant scholarship. Second, we gather evidence from different streams of literature, including sustainability reporting (Boura et al, 2020; Cabeza‐García et al, 2018), strategic leadership (Papagiannakis & Lioukas, 2018; Yamak et al, 2019), environmental management (Eiadat & Fernández Castro, 2018), and more, providing a holistic understanding of climate change disclosure. Third, although we find that the outcome dimension is less examined compared with the antecedent dimension, we highlight some critical gaps in both that suggest a future research agenda.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some research has shown that rigorous environmental guidelines can limit managerial decision capacity [81], raise costs, and force firms to make unprofitable investments [82], and even slow down the momentum of firms for the adoption of environmental practices [83], [84]. Other empirical evidence indicates that rigorous environmental regulation can lead to the reallocation of R&D toward pollution management and not toward the adoption of CE practices [85], [86]. These conflicting research findings can be explained, due to the fact that the literature has not analyzed the nonlinearity between the different institutional pressures on the adoption of CE practices by firms.…”
Section: A Intensity Of Innovation and Financial Support Institutiona...mentioning
confidence: 99%
“…Of course, top managers are expected to align their firm-level environmental climate with formal regulatory institutions if the regulatory requirements are perceived to be moderately stringent (Eiadat and Fern andez-Castro 2018), strongly enforced (Heyes 2000), efficient (Niosi 2002), predictable (Engel 2005), and procedurally fair (Tyler 2006). Indeed, "the realities of the organization are understood only as they are perceived by members of the organization, allowing climate to be viewed as a filter through which objective phenomena must pass" Stringer 1968, 43, as cited in Mayer, Kuenzi, andGreenbaum 2010, 10).…”
Section: Formal Regulatory Institutions Environmental Climate and Strategic Environmental Actionsmentioning
confidence: 99%